2022
DOI: 10.1002/uog.24756
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of deep and ovarian endometriosis in early pregnancy: ultrasound diagnostic study

Abstract: What are the novel findings of this work?Deep endometriosis and ovarian endometrioma were found to be relatively common in women attending for an early pregnancy ultrasound assessment and were often asymptomatic. Decidualization of the lesions was frequently observed. The presence of endometriosis was associated with a history of subfertility and presence of other pelvic abnormalities. What are the clinical implications of this work?This is the first study to report on the prevalence and morphological appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
4
15
4
Order By: Relevance
“…However, no detailed information on locations of the lesions is available. A publication on 1341 pregnant women reported ultrasound‐based prevalence of endometriosis during early pregnancy being 4.9%, endometrioma being found in 2.5% and deep endometriosis in 4.3% of women 37 . Prevalence of endometriosis is much lower in this study than in ours and population selection and indication for ultrasound might explain the discrepancy.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…However, no detailed information on locations of the lesions is available. A publication on 1341 pregnant women reported ultrasound‐based prevalence of endometriosis during early pregnancy being 4.9%, endometrioma being found in 2.5% and deep endometriosis in 4.3% of women 37 . Prevalence of endometriosis is much lower in this study than in ours and population selection and indication for ultrasound might explain the discrepancy.…”
Section: Discussioncontrasting
confidence: 84%
“…A publication on 1341 pregnant women reported ultrasound‐based prevalence of endometriosis during early pregnancy being 4.9%, endometrioma being found in 2.5% and deep endometriosis in 4.3% of women. 37 Prevalence of endometriosis is much lower in this study than in ours and population selection and indication for ultrasound might explain the discrepancy. Moreover, women with endometriosis might have lower pregnancy rates, therefore women who conceive would have lower prevalence of endometriosis.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Our study is the first to analyze reproductive and gynecological outcomes with regard to the morphological subtype of the unicornuate uterus. Our diagnostic approach for detecting endometriosis and adenomyosis has been used in previous large‐scale prospective studies and has been shown to be effective and accurate 26 , 30 , 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…For diagnosis of OE, not only is ultrasonography a very effective and straightforward tool [ 13 ], CA-125 and CA19-9 levels have also been recommended as useful markers [ 14–16 ]. Ruptured OE is rare.…”
Section: Introductionmentioning
confidence: 99%